2010
DOI: 10.2147/opth.s9969
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ knowledge and perspectives on wet age-related macular degeneration and its treatment

Abstract: Summary:There have been no studies examining the level of understanding age-related macular degeneration (ARMD) patients have about their disease, or their perceptions about intraocular injections as treatment. In this study, patient knowledge about ARMD risk factors was low but patients appeared more optimistic than fearful when confronted with intraocular antivascular endothelial growth factor (anti-VEGF) injections as treatment.Purpose:In recent years there has been an increase in our understanding of wet A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
3
16
1
1
Order By: Relevance
“…Thus, DITAMD should be tested in additional sites, preferably in a multicentre, international setting. However, the strength of the current study is its coherence with previous studies that report similar dimensions of importance in nAMD treatment (Kandula et al 2010(Kandula et al , 2010Boyle et al 2015;Senra et al 2016Senra et al , 2017. Kandula et al reported that the patients felt hopeful about the prospect of receiving intravitreal injections which is similar to one of our most frequently reported dimensions: receive treatment to keep vision.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, DITAMD should be tested in additional sites, preferably in a multicentre, international setting. However, the strength of the current study is its coherence with previous studies that report similar dimensions of importance in nAMD treatment (Kandula et al 2010(Kandula et al , 2010Boyle et al 2015;Senra et al 2016Senra et al , 2017. Kandula et al reported that the patients felt hopeful about the prospect of receiving intravitreal injections which is similar to one of our most frequently reported dimensions: receive treatment to keep vision.…”
Section: Discussionsupporting
confidence: 79%
“…However, the strength of the current study is its coherence with previous studies that report similar dimensions of importance in nAMD treatment (Kandula et al 2010(Kandula et al , 2010Boyle et al 2015;Senra et al 2016Senra et al , 2017. Further, 89% of the patients preferred to get more information, indicating the importance of information (Kandula et al 2010). Further, 89% of the patients preferred to get more information, indicating the importance of information (Kandula et al 2010).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In einer US-amerikanischen Befragung wussten immerhin 48 % der AMD-Patienten, dass familiäre Belastung das Erkrankungsrisiko beeinflusst [6]. In der Tat weisen aktuelle Informationsmaterialien zur AMD (Abb.…”
Section: Wahrnehmung Und Akzeptanz Von Risiken Bei Der Amdunclassified